An Exquisite Corpse: Unfolding Scarcity Using Arts-Based Autoethnography - Green, Deborah (Art/Research International, 2024)
After 14 complex years, I message him: “I keep saving you and losing me.” M hangs himself. Numbly I sit holding M’s cold dead hand in my warm shaking one. I’m 33. A widow. Twenty years on, and now a creative arts therapist/educator/researcher, I launched an arts-based autoethnographic (abr+a) quest to exhume and frankly face my role within my husband’s suicide. Naively, I imagined cultivating an ecotone where self-care and care-for-other intra-act. Lured by this poietic methodological experiment, Scarcity-Gargoyle, however, sloped in— an inner-alter symbolising a trauma-response that had outlived its usefulness. Leading a motley crew of author, animangels, Darwin, and new material/posthumanists, it incited a gyroscopically-circling contemplation of trauma and scarcity, now folded into this Exquisite Corpse game. As this game unfurls, the question lingers within creases and crevices: What might these critters speak/sing/growl/howl/whisper/rasp to the lofty aspiration of crafting capacity for simultaneous compassionate becoming-with self and other?